The Rise and Fall of the Pyramid Schemes in Albania - Jarvis, Christopher (IMF Working Papers; Working Paper, 1999)
What lessons can be drawn from the unprecedented growth and spectacular collapse of financial pyramid schemes in Albania? This paper discusses the origins of the pyramid schemes and the way the authorities handled them. It also analyzes the economic effects of the pyramid schemes, concluding that despite the descent into anarchy triggered by the schemes' collapse their direct effects on the economy are difficult to specify and appear to have been limited. Finally, the paper argues that prevention of pyramid schemes is better than cure, and that governments and international financial institutions should be vigilant in clamping down on frauds.